Blood phosphorus and magnesium levels in 130 elite track and field athletes - Malliaropoulos, N.; Tsitas, K.; Porfiriadou, A.; Papalada, A.; Ames, P. R.; del Buono, A.; Lippi, G.; Maffulli, N. (Asian Journal of Sports Medicine, 2013)
Purpose: This study tested the clinical utility and relevance of serum phosphorus and magnesium as markers possibly useful to monitor training in athletes.